Pengimplementasian ISAK 35 Pada Laporan Keuangan Organisasi Non Laba Di Panti Asuhan Nobel Pelita Anak Bangsa Dan Panti Asuhan Terang Fajar - Purba, Sahala; Sitohang, Santy Aji; Butar Butar, Erissa Antheresya; Hutagalung, Dewi Delima; Sitanggang, Ema Mastaria; Simbolon, Sofia Imelda; Gracella, Sarah; Manullang, Novelita; Natalia, Vebina (Jurnal Pengabdian Kepada Masyarakat, 2023)
This counseling is aimed at the development of non-profit organizations which are currently mushrooming a lot, one of which is the orphanage. One way that can be done to develop the orphanage is to increase the trust of donors in donating funds which can be reached by applying ISAK 35 to its financial reporting as a form of transparency from the orphanage. ISAK 35 is an accounting standard that regulates the presentation of financial statements of non-profit organizations. This counseling was carried out using an interview method involving one administrator and owner of the orphanage. This counseling was carried out in two days, namely December 19 and 20, 2023, from the findings of this service that the orphanage has taken responsibility for donors based only on proof of purchase invoices. With this counseling, it is hoped that the Nobel Pelita Orphanage and the Terang Fajar Children's Orphanage can prepare their financial reports according to the applicable standards, namely ISAK 35 and will produce financial reports consisting of a Statement of Financial Position, a Comprehensive Income Statement, a Statement of Cash Flows and Notes to Reports Finance.